2016
DOI: 10.1007/s00704-016-1890-y
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the WRF model to simulate the seasonal and interannual variability of hydrometeorological variables in East Africa: a case study for the Tana River basin in Kenya

Abstract: This study investigates the ability of the regional climate model Weather Research and Forecasting (WRF) in simulating the seasonal and interannual variability of hydrometeorological variables in the Tana River basin (TRB) in Kenya, East Africa. The impact of two different land use classifications, i.e., the Moderate Resolution Imaging Spectroradiometer (MODIS) and the US Geological Survey (USGS) at two horizontal resolutions (50 and 25 km) is investigated. Simulated precipitation and temperature for the perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 33 publications
(49 reference statements)
1
35
0
Order By: Relevance
“…This could be attributed to the coverage of the gauge rainfall, which comes from only three stations and which is not fully representative for the whole subcatchment unlike CHIRPS and TRMM data, which takes averaged values over the whole subcatchment. In general, however, the gauge rainfall and TRMM over MSS agree very closely in terms of their annual and interannual variability consistent with previous studies (e.g., Kerandi et al 2016). This is also the case with CHIRPS datasets compared with the gauge rainfall (r (44) = 0.92, p < 0.001).…”
Section: Precipitation and Dischargesupporting
confidence: 90%
See 2 more Smart Citations
“…This could be attributed to the coverage of the gauge rainfall, which comes from only three stations and which is not fully representative for the whole subcatchment unlike CHIRPS and TRMM data, which takes averaged values over the whole subcatchment. In general, however, the gauge rainfall and TRMM over MSS agree very closely in terms of their annual and interannual variability consistent with previous studies (e.g., Kerandi et al 2016). This is also the case with CHIRPS datasets compared with the gauge rainfall (r (44) = 0.92, p < 0.001).…”
Section: Precipitation and Dischargesupporting
confidence: 90%
“…1), like most parts of East Africa, receives its rainfall in two seasons during March, April, and May (MAM) and October, November, and December (OND) locally known as the Blong rains^and Bshort rains,^respectively, due to the south-north oscillation of the Intertropical Convergence Zone (ITCZ) (Kitheka et al 2005;Nakaegawa and Wachana 2012;Oludhe et al 2013). The mean annual rainfall ranges between 960 and 1200 mm, while climatologically, the region experiences low annual/monthly mean temperatures of about 17°C or less (Kerandi et al 2016). According to the Moderate Resolution Imaging Spectroradiometer (MODIS, 20 classes; Friedl et al 2002) based land use classification, the dominant land use classes are the evergreen broadleaf forest and the savannas and woody savannas (Fig.…”
Section: The Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the negative trends observed during pre‐2009 (though insignificant) interprets that EA experienced low AOD attributed to lower population (by then), characterized by reduced anthropogenic activities, shrunken economic growth and sparse industries (Makokha et al , ; Boiyo et al , ). In contrast, increasing AOD trends during the entire period and post‐2009 indicates an increase in the aerosol loading attributed to: (1) population growth leading to increased anthropogenic activities (Gatebe et al , ; Ngaina and Muthama, ), (2) industrialization resulting to increased anthropogenic emissions (Mabasi, ; Ngo et al , ) and (3) climate change occasioned by increased temperature and reduced precipitation (Yang et al , ; Kerandi et al , ). These results in increased photochemical processes with reduced deposition and increased emission of dust aerosols from the arid and semi‐arid regions of EA.…”
Section: Resultsmentioning
confidence: 99%
“…The monthly averaged temperature, wind speed and relative humidity at 850 hPa and spatial resolution of 0.75 × 0.75° were sourced from the European Centre for Medium‐Range Weather Forecasts (ECMWF), previously used by a number of authors over EA (Yang et al ., ; Ogwang et al ., ). However, the Climate Research Unit (CRU) temperature (Harris et al ., ) and Tropical Rainfall Measuring Mission (TRMM) (Huffman et al ., ) precipitation data sets derived at spatial resolutions of 0.5 × 0.5° and 0.25 × 0.25°, respectively, were preferred due to their better performance over the region (Kerandi et al ., ; Makokha et al ., ).…”
Section: Methodsmentioning
confidence: 98%